Workplace Exposures and Prescription Drug Misuse Among Nurses. (18th November 2022) - Trinkoff, Alison M.; Selby, Victoria L.; Baek, Hyang; Storr, Carla L.; Steele, Jenell; Han, Kihye
Abstract : OBJECTIVE: This study examined the association between workplace exposure and prescription drug misuse in nurses. BACKGROUND: Studies have found RNs and other health providers have higher rates of prescription misuse than the general population and have suggested that workplace exposures along with excessive job demands create circumstances fostering misuse. METHODS: Survey data from 1170 RNs on workplace exposures (availability, frequency of administration, knowledge of substances, and workplace controls) were described by workplace, position, and specialty. Exposures were then related to prescription drug misuse using logistic regression. RESULTS: Each workplace exposure was associated with past year prescription drug misuse. An index combining all exposures was significantly related to misuse ( P = 0.001), and odds of misuse increased by 38% for each point increase in the exposure index. CONCLUSIONS: Consideration of the health and well-being of nurses at higher odds of exposure to prescription drugs with misuse potential is warranted. Workplace support to help nurses maintain and restore their health should be a priority.